The vital few versus the trivial many : - Muzea, George (Wiley, 2005)
Filled with in-depth insight and expert advice, The Vital Few vs. The Trivial Many will open your eyes to a new way of looking at the investment world, especially the stock market. You'll discover how to look past media hype to discern what the Vital Few or corporate insiders—those who know their companies best—are doing. By explaining which information is accurate and valuable, as opposed to that which is misleading and financially hazardous, investment professional George Muzea will show you how to successfully and intelligently evaluate the stock market and find valuable gems that have yet to be discovered by the masses.